PEMANFAATAN SIMBIOSIS MIKROALGA Chlorella sp. DENGAN VARIASI PENAMBAHAN AGROBOST UNTUK MENURUNKAN KADAR PENCEMARAN PABRIK KELAPA SAWIT - Angelia Angelia; Fajar Restuhadi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to get the best of microalgae (Chlorella sp.) symbiosis with variation of Agrobost to decreasing  pollution level of palm oil mill effluent (POME) according to standard quality.  This research used a completely randomized design (CRD) with 5 treatments and 3 replications.  The  treatments  in this addition was microalgae Chlorella sp. as much 800 ml/L (Abundance of cells 6,3 x 106 cell/ml) of POME with some variations concentrations of Agrobost (0%, 1%, 2%, 3%, and 4%).  The data obtained were analyzed statistically using ANOVA and DNMRT at 5% level.  The result showed that the addition of Agrobost had significant affect for DO, Nitrate, and Phosphate.  The treatment chosen from the result of this research was the P4treatment showed the highest level of reduction which had the value of Phospate of 61,05%, Nitrate of 77,63%, and increases in the DO of 564,49%. Keywords: Palm oil mill effluent, microalgae Chlorella sp., Agrobost.